2014
DOI: 10.1371/journal.pone.0112195
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Traffic Air Pollution inside and outside a Road Tunnel in Shanghai, China

Abstract: To investigate the vehicle induced air pollution situations both inside and outside the tunnel, the field measurement of the pollutants concentrations and its diurnal variations was performed inside and outside the Xiangyin tunnel in Shanghai from 13:00 on April 24th to 13:00 on April 25th, 2013. The highest hourly average concentrations of pollutants were quantified that CO, NO, NO2 and NOX inside the tunnel were 13.223 mg/m3, 1.829 mg/m3, 0.291 mg/m3 and 3.029 mg/m3, respectively, while the lowest ones were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 17 publications
3
19
0
Order By: Relevance
“…For the eBC source apportionment in Xi'an, Angstrom exponents of 0.9 and 1.7 were considered for traffic and wood burning, respectively, following the suggestions in Zotter et al (2016) presenting a re-evaluation of the method developed in Sandradewi et al (2008). The eBC wb to BBOA ratio was found to be 0.14, which is in good agreement with previous reported values (Gilardoni et al, 2011;Zotter et al, 2014). The ratio eBC tr to HOA was 0.79, which is lower than the ratios reported in previous European studies (El Haddad et al, 2013 and references therein), but is in good agreement with results derived from measurements in China (Huang et al, 2012;Zhou et al, 2014).…”
Section: Ebc Source Apportionmentsupporting
confidence: 85%
“…For the eBC source apportionment in Xi'an, Angstrom exponents of 0.9 and 1.7 were considered for traffic and wood burning, respectively, following the suggestions in Zotter et al (2016) presenting a re-evaluation of the method developed in Sandradewi et al (2008). The eBC wb to BBOA ratio was found to be 0.14, which is in good agreement with previous reported values (Gilardoni et al, 2011;Zotter et al, 2014). The ratio eBC tr to HOA was 0.79, which is lower than the ratios reported in previous European studies (El Haddad et al, 2013 and references therein), but is in good agreement with results derived from measurements in China (Huang et al, 2012;Zhou et al, 2014).…”
Section: Ebc Source Apportionmentsupporting
confidence: 85%
“…and traffic exhausts fumes (0.5-1.3) (Zhou et al, 2014;He et al, 2008), indicating that coal combustion and traffic exhaust fumes were the major primary sources at all sites. Beijing (2.6) and Xinxiang (3.3) were mainly dominated by coal combustion emissions.…”
Section: Source Apportionment Of Different Carbon Fractionsmentioning
confidence: 94%
“…In a study by Rosenfeld et al (2008) pollution may increase or decrease precipitation depending on other environmental factors, indicating that the relationship is not still clear. Overall, a positive relation between maximum and average temperature and air pollution is documented in earlier studies, while a negative relationship between minimum temperature and wind speed is found (Roberts, 2004;Tai et al, 2010Tai et al, , 2012Barmpadimos et al, 2012;Lecoeur et al, 2012;Zhou et al, 2014;Price et al, 2014).…”
Section: Summary Statisticsmentioning
confidence: 78%